Carbamazepine and oxcarbazepine, but not eslicarbazepine, enhance excitatory synaptic transmission onto hippocampal CA1 pyramidal cells through an antagonist action at adenosine A1 receptors. (June 2015) - Booker, Sam A.; Pires, Nuno; Cobb, Stuart; Soares-da-Silva, Patrício; Vida, Imre
Abstract: This study assessed the anticonvulsant and seizure generation effects of carbamazepine (CBZ), oxcarbazepine (OXC) and eslicarbazepine (S-Lic) in wild-type mice. Electrophysiological recordings were made to discriminate potential cellular and synaptic mechanisms underlying anti- and pro-epileptic actions. The anticonvulsant and pro-convulsant effects were evaluated in the MES, the 6-Hz and the Irwin tests. Whole-cell patch-clamp recordings were used to investigate the effects on fast excitatory and inhibitory synaptic transmission in hippocampal area CA1. The safety window for CBZ, OXC and eslicarbazepine (ED50 value against the MES test and the dose that produces grade 5 convulsions in all mice), was 6.3, 6.0 and 12.5, respectively. At high concentrations the three drugs reduced synaptic transmission. CBZ and OXC enhanced excitatory postsynaptic currents (EPSCs) at low, therapeutically-relevant concentrations. These effects were associated with no change in inhibitory postsynaptic currents (IPSCs) resulting in altered balance between excitation and inhibition. S-Lic had no effect on EPSC or IPSC amplitudes over the same concentration range. The CBZ mediated enhancement of EPSCs was blocked by DPCPX, a selective antagonist, and occluded by CCPA, a selective agonist of the adenosine A1 receptor. Furthermore, reduction of endogenous adenosine by application of the enzyme adenosine deaminase also abolished the CBZ- and OXC-induced increase of EPSCs, indicating that the two drugs act as antagonists at native adenosine receptors. In conclusion, CBZ and OXC possess pro-epileptic actions at clinically-relevant concentrations through the enhancement of excitatory synaptic transmission. S-Lic by comparison has no such effect on synaptic transmission, explaining its lack of seizure exacerbation. Highlights: Carbamazepine and oxcarbazepine possess pro-epileptic actions. Eslicarbazepine lacks seizure exacerbation. Carbamazepine and oxcarbazepine enhance excitatory synaptic transmission. Eslicarbazepine does not enhance synaptic transmission. Antagonism of A1 adenosine receptors can explain the pro-epileptic effects.